High-quality nitrogen-doped graphene films synthesized from pyridine via two-step chemical vapor deposition - Son, Myungwoo; Chee, Sang-Soo; Kim, So-Young; Lee, Wonki; Kim, Yong Hyun; Oh, Byoung-Yun; Hwang, Jun Yeon; Lee, Byoung Hun; Ham, Moon-Ho (PERGAMON-ELSEVIER SCIENCE LTD, 2020)
Modulation of the electrical properties of graphene is of significant importance in advancing graphene electronics: it can be achieved by a Fermi level shift induced by electron acceptor/donor doping. Suitable doping methods involving low-temperature processes and offering long-term stability are imperative to practical applications for such materials. Here, we demonstrate a two-step chemical vapor deposition (CVD) technique for direct synthesis of N-doped graphene film from a pyridine feed-stock at 300 degrees C under ambient pressure. We extended the synthesis-classified into nucleation and lateral growth steps-by controlling the carbon partial pressure in the processing gases. This led to large-area, continuous N-doped graphene films of excellent quality with full surface coverage: for example, a film size of 2 in(2), optical transmittance of 97.6%, and electron mobility of 1400 cm(2) V-1 s(-1). Our modified CVD method is expected to facilitate the direct synthesis of N-doped graphene in device manufacturing processes toward practical applications while keeping the underlying devices intact. (C) 2020 Elsevier Ltd. All rights reserved.
Keywords: LOW-TEMPERATURE GROWTH